PENGARUH PENGGUNAAN METODE FUN LEARNING UNTUK MENUMBUHKAN SEMANGAT SISWA KELAS III UPT SDN 23 GRESIK - Rafidatul Hidayah; Afakhrul Masub Bakhtiar (STKIP Subang, 2022)
Abstract The quality of student learning outcomes is caused by two factors, namely internal and external factors. Experienced internal factors and factors that influence student learning processes and internalized outcomes include, attitudes towards learning, interest and motivation to learn, learning concentration, while external factors include things such as, teachers as learning coaches, infrastructure and learning facilities. Less effective and inadequate learning, the quality and knowledge of UPT SDN 23 Gresik students also become not smart and capable. To overcome these problems, the development of the fun learning method was implemented at UPT SDN 23 Gresik. With the fun learning method, students play while learning to create a fun and not boring atmosphere. Aims to increase the taste and intelligence at UPT SDN 23 Gresik on an ongoing basis. The result is that students become more excited to go to school, students become happy and interested in teaching and learning activities because the fun learning method is not boring. Keywords : Fun Learning, Learning Effect, Enthusiasm